Vidas no sufoco nos transportes na pandemia: um App de mapeamento colaborativo para alerta de lotação na Região Metropolitana de São Paulo (RMSP) - Ricardo Barbosa da Silva (Confins)
Crowding in public transport is a historical problem in the metropolis of São Paulo, but it has become even worse in the context of the new coronavirus pandemic, called SARS-CoV-2. The objective of this article is to understand the crowded condition of public transportation in the metropolitan área of São Paulo (RMSP) in its relation to the groups most vulnerable to Covid-19 in the territory. For this, a methodology with a quantitative and qualitative approach was used, the first based on data on mobility, crowding in public transport and deaths by Covid-19, as well, data collected in collaborative digital mapping, from alerts of people in crowded condition in public transport in RMSP, through the application (App) Sufoco. Documentary analysis was also used, based on the decrees and resolutions related to the public management of the pandemic. It was found that the population of the urban peripheries is most subjected to the condition of suffocation of crowding in public transport, precisely in the territory that concentrates the poorest and blacks, found to be the most vulnerable group to Covid-19.